Risk factors affecting relapse after discontinuation of biologics in children with Crohn's disease who maintained deep remission - Kim, Hansol; Kim, Yoon Zi; Kim, Seon Young; Choe, Yon Ho; Kim, Mi Jin (Frontiers in Pediatrics, 2024)
Objectives: Biologics are important therapeutic agents for pediatric Crohn’s disease. Discontinuation of biologics is known to increase the relapse rate up to 71.4% in these patients; however, their long-term use increases the risk of opportunistic infections and causes economic burden and psychological fatigue. Therefore, taking a drug holiday is meaningful, even if the biologics cannot be completely discontinued. This study aimed to analyze the risk factors affecting relapse after discontinuation of biologics in children with Crohn’s disease. Methods: We retrospectively reviewed the data of 435 children with Crohn’s disease who visited a single health center between March 2013 and March 2021. Subsequently, we analyzed data from the patients who discontinued biologics after deep remission. Results: Among the enrolled patients, 388 were followed up for ≥2 years, and of these, 357 were administered biologics. A total of 103 patients discontinued biologics after deep remission, subsequently 31 maintained remission and 72 relapsed. The shorter the duration of biologic treatment (odds ratio of 0.444, P=0.029), the higher the ESR (odds ratio of 1.294, P=0.009) and fecal calprotectin (odds ratio of 1.010, P=0.032), and the less histological remission at the time of discontinuation of biologics (odds ratio of 0.119, P=0.026), the greater the risk of relapse after discontinuation of biologics. Conclusions: We identified factors associated with relapse after discontinuation of biologics. The results suggest that biologics can be discontinued in the absence of these factors after deep remission. However, because the relapse rate may increase after the discontinuation of biologics, close monitoring is important, and if necessary, re-administration of biologics should be actively considered.